ANALYSIS OF RED CHILLI AND COR INTERCROPPING FARMING BUSINESS WITH ESTIMATED LAND USE RATIO IN PANJI PORSEA VILLAGE, SITINJO DISTRICT, DAIRI DISTRICT - Sangkot Pahisar Siboro; Retna Astuti; Tumpal HS Siregar (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
This research aims to analyze how farming works, the effectiveness of utilization and aspects of red and corn production intercropping red chilies and corn with production functions in Panji Porsea Village, Sitinjo District, Dairi Regency. This research was carried out in November 2022. The form of this research was a quantitative method. The population in this study were 50 farmers using corn monoculture, chili monoculture and intercropping red chili with corn. To obtain appropriate research results, the sample used was purposive sampling taken from each village, the data analysis technique used was cost and revenue analysis and Land Use Ratio Analysis.intercropping chili corn.The effectiveness of intercropping land use for red chilies and corn is running very well, because the intercropping system at the time of planting is very suitable and very feasible to implement, able to increase the income of both chili and corn farmers. The production aspect of red chilies and corn after using the intercropping method appears to increase when compared to monoculture because by saving land you can produce 2 different productions.